Multidetector computed tomography diagnosis of adenomyomatosis of the gallbladder - Aysel Türkvatan; Mehmet Akif TÜRKOĞLU; Yusuf Alper ÖZOĞUL; Alper KARACAN; Musa AKOĞLU (Turkish Journal of Gastroenterology, 2019)
-